Enhanced piezoelectric nanogenerator based on tridoped graphene and Ti3CNTx MXene Quasi-3D heterostructure - Kou, Lijie; Haque, Rawhan; Sadri, Rad; Auliya, Rahmat Zaki; Kaur, Manpreet; Roberts, Edward P. L.; Gan, Wee Chen; Mohammad Haniff, Muhammad Aniq Shazni; Dee, Chang Fu; Ooi, Poh Choon (American Chemical Society, 2024)
The demand for self-powered wearables is surging, as consumers seek convenience and portability. Energy-harvesting technologies, especially piezoelectric nanogenerators (PENGs), which convert mechanical energy to electrical energy, hold promise for harvesting human motion energy. Hence, ongoing research aims to enhance the output power efficiency and integrate nanogenerators with flexible materials. This involves material innovation to boost PENG performance, optimizing structure for flexibility, and improving manufacturing for scalable and cost-effective production. In this study, heterostructure nanofiller based on interfacial interaction was formed by mixing nitrogen, sulfur, and phosphorus tridoped graphene (NSPG) and Ti3CNTx MXene in an appropriate ratio, which produces a synergistic enhancement effect in the PENG’s electrical output performance. According to X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, X-ray diffractometer (XRD), and Fourier transform infrared spectroscopy (FTIR) chemical characterization analysis, it is proposed that the excellent conductivity and rich surface functional groups of these two-dimensional materials can effectively provide heterointerfaces to form a quasi-three-dimensional heterostructure and improve the interaction between the fillers and polymer matrix, promoting the electroactive β-phase, and consequently enhancing the output power density of PENG. NSPG and Ti3CNTx, with their remarkable electronic and chemical properties, were prepared using an environmentally friendly electrochemical exfoliation method. The short-circuit current of PENG can be improved to 1.48 μA, and the open-circuit voltage can be increased to 14.6 V, 5-fold compared to pure PVDF, and the output power density, PA, reaches 2.2 μW/cm2. When attached to different parts of the human body, the PENG can practically produce electrical signals, which can be rectified using a full-wave bridge rectifier and used to charge a capacitor and light up LEDs. This study establishes a robust connection between multifaceted heterostructures and flexible wearable energy harvesters, offering promising prospects for advancing flexible, sensitive, and self-powered electronics.